Manufacturing and Characterization of Bioplastic from Chitosan and Rambutan Seed (Nephelium lappaceum L.) Starch with the Addition of Sorbitol as Plasticizer - Kusumaningsih, Triana; Firdaus, Maulidan; Handayani, Desi; Rahayu, Windi Vinata; Vegasty, Sabella; Ningsih, Dyah A F; Istiqomah, Annisa (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
A bioplastic formulated from chitosan and rambutan seed starch (Nephelium lappaceum L.), with sorbitol added as a plasticizer, presents a promising innovation to reduce the reliance on conventional plastics, which contribute to an annual waste accumulation of 381 million tons. This study aims to produce bioplastic from chitosan and rambutan seed starch, to analyze its physical and mechanical properties, and to determine the optimal composition. The bioplastic was fabricated using the solution casting method, with heating at 85-95◦C and drying in an oven at 60◦C for approximately 24 hours. The resulting bioplastic exhibited favorable tensile strength and elongation, as well as rapid biodegradability in soil. FTIR analysis revealed functional groups including O-H, C-H, N-H, C-O, and C-C, indicating the presence of corresponding components. The best composition was achieved with a starch-to-chitosan ratio of 40:60% and 20% sorbitol, resulting in a thickness of 0.21 mm, density of 0.80 g/cm3, water absorptionof 41.17%, tensile strength of 52.53 N/mm2, elongation of 22.64%, and biodegradability of 36.67%. TGA analysis showed three degradation stages i.e. water dehydration, starch degradation, and chitosan degradation.